Overview of Team Cooperation in Handling Emergency Cases at H. Abdul Manap Jambi Hospital - Br Bangun, Hosma; Mawarti, Indah; Martawinarti, Rts Netisa; Yusnilawati; Subandi, Andi (Jurnal Pinang Masak, 2026)
Background: The Emergency Department (ED) plays a strategic role as the frontline in managing life-threatening emergency cases. The success of this management heavily depends on the effectiveness of teamwork through interprofessional collaboration among physicians, nurses, and midwives. This study aims to describe teamwork in the management of emergency cases at the ED of RSUD H. Abdul Manap, Jambi City Methods: This study employed a descriptive quantitative approach with a total sampling technique involving all 34 healthcare professionals in the ED of RSUD H. Abdul Manap, Jambi City (6 physicians, 17 nurses, and 11 midwives). Data were collected using a questionnaire measuring four main components of teamwork and role clarity, which had been tested for validity (r calculated > r table 0.361) and reliability (Cronbach's Alpha 0.967), and subsequently analyzed using univariate analysis. Results: The results showed that the majority of respondents were female (64.7%), in the 30–39 age group (73.5%), worked as nurses (50%), and had a length of service > 3 years (58.8%). All respondents (100%) perceived the role clarity of physicians, nurses, and midwives to be in the good category. Meanwhile, regarding the overall teamwork variable, 31 respondents (91.2%) rated it in the good category, and 3 respondents (8.8%) rated it in the fair category. Conclusion: All respondents rated the role clarity of physicians, nurses, and midwives as excellent, and teamwork in handling emergency cases was generally perceived as good. The hospital is recommended to maintain these achievements by strengthening open two-way communication and the active contribution of all professions in the ED.